The Interaction Between Flexible Plates and Fluid in Two-dimensional Flow - Jia, Laibing (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2014)
The fascinating rainbow colors we see in soap film not only delight us; they also help us understand the physical essence of nature. In this dissertation, the author presents his studies on the interactions between flexible bodies and ambient fluids, a topic reflected in nature, in everyday life, and in various industrial applications. By investigating this topic, he reveals the mechanism of flow-induced vibration of flexible bodies, the process of energy exchange between flexible bodies and fluids, and the way flexible bodies interact with each other in flowing fluids. These studies not only allow us to understand nature better, but can also help us invent new machines and improve existing devices to glean more energy from nature.